Site Preference in Multimetallic Nanoclusters: Incorporation of Alkali Metal Ions or Copper Atoms into the Alkynyl‐Protected Body‐Centered Cubic Cluster [Au7Ag8(C≡CtBu)12]+. (3rd November 2016) - Wang, Yu; Su, Haifeng; Ren, Liting; Malola, Sami; Lin, Shuichao; Teo, Boon K.; Häkkinen, Hannu; Zheng, Nanfeng
Abstract: The synthesis, structure, substitution chemistry, and optical properties of the gold‐centered cubic monocationic cluster [Au@Ag8 @Au6 (C≡C t Bu)12 ] + are reported. The metal framework of this cluster can be described as a fragment of a body‐centered cubic (bcc) lattice with the silver and gold atoms occupying the vertices and the body center of the cube, respectively. The incorporation of alkali metal atoms gave rise to [Mn Ag8− n Au7 (C≡C t Bu)12 ] + clusters ( n =1 for M=Na, K, Rb, Cs and n =2 for M=K, Rb), with the alkali metal ion(s) presumably occupying the vertex site(s), whereas the incorporation of copper atoms produced [Cun Ag8 Au7− n (C≡C t Bu)12 ] + clusters ( n =1–6), with the Cu atom(s) presumably occupying the capping site(s). The parent cluster exhibited strong emission in the near‐IR region ( λ max =818 nm) with a quantum yield of 2 % upon excitation at λ =482 nm. Its photoluminescence was quenched upon substitution with a Na + ion. DFT calculations confirmed the superatom characteristics of the title compound and the sodium‐substituted derivatives.